Silicon carbon material, preparation method thereof and lithium ion battery
By adding organic trivalent iron salts in the process of preparing porous carbon, the mesoporous proportion, nitrogen doping and carbon nanotube growth of silicon carbon materials are optimized, and the problem of poor performance of existing silicon carbon materials in lithium-ion batteries is solved, achieving high strength and excellent battery performance.
Patent Information
- Application Number
- CN202411863001.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing silicon-carbon anode materials are difficult to take into account high energy density, high cycle performance, high rate performance and high environmental adaptability in lithium-ion batteries, and their strength is low, voltage-tolerant, and their rate performance is poor.
By adding organic trivalent iron salts in the preparation of porous carbon, the mesoporous proportion of silicon carbon materials, nitrogen doping in silicon deposition and in-situ growth of carbon nanotubes are optimized, and the conductivity and strength of the material are improved.
The high strength and excellent performance of silicon-carbon materials are achieved, and the overall performance of the battery is significantly improved after being used in lithium-ion batteries.
Smart Images

Figure CN119725443A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] With the development of the times, the current lithium-ion battery technology is increasingly unable to meet people's needs for production and life. People are in urgent need of a lithium-ion battery with ultra-high energy density, ultra-high cycle performance, ultra-high rate performance, and ultra-high environmental adaptability. For existing technologies, the emergence and development of silicon-carbon negative electrode materials is undoubtedly a powerful lever to promote the development of high-performance lithium-ion batteries.
[0003] However, the existing silicon-carbon negative electrode materials, although their gram capacity is relatively high, are mostly made by silane deposition of porous carbon materials, which have low strength and are not pressure-resistant. In addition, low-temperature deposition technology can easily lead to poor battery rate performance. Generally speaking, the expansion of silicon-carbon negative electrode materials after lithium insertion is often limited by the strength of porous carbon. Porous carbon with low expansion has high strength, while porous carbon with high expansion has low strength. In addition, porous carbon is mostly obtained by activating hard carbon. Although activation is conducive to its development towards graphitization, the resulting battery rate performance is still poor. It is difficult to activate carbon material precursors with excessive graphitization, and the layered structure contained also affects the uniformity of silane deposition.
[0004] Due to the many contradictions between strength performance, rate performance, expansion performance, cycle performance, and environmental adaptability performance, in order to produce lithium-ion batteries with excellent comprehensive performance, silicon-carbon materials also need to be combined with various ingredients in the positive and negative electrode formulas and electrolyte formulas, especially additives to improve related performance, or need to be combined with various advanced technologies such as extremely low copper foil, extremely low electrode thickness, laser drilling technology, laser cleaning technology, pole ear centering technology, double-layer coating, multiple pole ears, full pole ears, and even full pole ears. Technology collaboration can achieve this.
[0005] Therefore, from the perspective of materials, there is an urgent need for a high-strength silicon-carbon material that can comprehensively improve rate performance, expansion performance, cycle performance, and environmental adaptability when used in batteries. Summary of the invention
[0006] In order to solve the defect that lithium ion batteries using porous silicon-carbon materials in the prior art are difficult to simultaneously take into account multiple excellent properties, the present invention provides a silicon-carbon material and a preparation method thereof, and a lithium ion battery. The preparation method can optimize the strength and other properties of the obtained silicon-carbon material, and after being used in lithium ion batteries, its rate, expansion, cycle and other properties can be comprehensively optimized and improved.
[0007] To achieve the above purpose, the present invention adopts the following technical solution.
[0008] The present invention provides a method for preparing a silicon-carbon material, and the method for preparing the silicon-carbon material comprises the following steps:
[0009] S1, drying a slurry of a carbonaceous material precursor and an iron salt to obtain a first precursor; wherein the iron salt comprises an organic trivalent iron salt;
[0010] S2, carbonizing and activating the first precursor to obtain a second precursor;
[0011] S3, performing a first vapor deposition on the second precursor to obtain a third precursor;
[0012] Wherein, the first deposition gas used in the first vapor deposition comprises a silicon source gas and a carrier gas; the silicon source gas comprises silane, and the carrier gas comprises nitrogen;
[0013] S4, performing a second vapor deposition on the third precursor to obtain the silicon-carbon material;
[0014] Wherein, the second deposition gas used in the second vapor deposition comprises a carbon source gas.
[0015] In the present invention, the inventors unexpectedly discovered that by adding an organic trivalent iron salt during the preparation of porous carbon, the porous carbon thus prepared can simultaneously achieve the following during the subsequent silane deposition and carbon deposition processes: increasing the mesopore ratio of the material, doping nitrogen during silicon deposition, and more controllably growing carbon nanotubes in situ, thereby achieving multiple goals at one stroke. The electrical conductivity, strength and other properties of the resulting silicon-carbon material can be optimized through a simple process, and then after being used in lithium-ion batteries, their rate, expansion, cycle and other properties can be comprehensively optimized and improved.
[0016] In the present invention, in step S1, the organic trivalent iron salt has a certain complexing effect and has good compatibility with the carbon material precursor, so that the organic trivalent iron salt can be extremely evenly dispersed in the carbon material precursor with higher viscosity. During the drying process, the large pores and above in the carbon material precursor will be eliminated first, thereby improving the overall strength of the material.
[0017] In some embodiments, in step S1, the organic ferric iron salt includes ferric acetate and / or ferric citrate.
[0018] In some embodiments, in step S1, based on the mass of the carbon material precursor, the molar amount of iron in the iron salt is 0.01-1 mol / kg, for example, 0.02 mol / kg, 0.04 mol / kg, 0.06 mol / kg, 0.08 mol / kg, 0.12 mol / kg, 0.14 mol / kg, 0.16 mol / kg or 0.25 mol / kg.
[0019] In the present invention, in step S1, the carbon material precursor may be a conventional carbon source for preparing carbon materials in the art, preferably including resin and / or biomass.
[0020] The resin preferably includes one or more of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine-formaldehyde resin, furan resin, silicone resin, polyester resin, polyamide resin, acrylic resin, polyurethane, vinyl resin, hydrocarbon resin and polyether resin.
[0021] The biomass preferably includes one or more of lignin, cellulose, hemicellulose and chitin.
[0022] In some embodiments, in step S1, the carbon material precursor includes one or more of phenolic resin, lignin and chitin.
[0023] In some embodiments, in step S1, the carbon material precursor includes a phenolic resin, and the slurry further includes a curing agent.
[0024] Wherein, the curing agent preferably includes hexamethylenetetramine.
[0025] Wherein, the mass ratio of the curing agent to the phenolic resin is preferably (0.005-1):1, such as 0.06:1.
[0026] In some embodiments, in step S1, the solvent in the slurry includes ethanol.
[0027] In some embodiments, in step S1, the mass ratio of the solvent in the slurry to the carbon material precursor is preferably (1-20):1, such as 2:1.
[0028] In some embodiments, in step S1, the drying method is spray drying.
[0029] In some embodiments, in step S1, the drying temperature is 70-200°C, for example, 130°C.
[0030] In some embodiments, in step S1, the particle size of the first precursor is 4-16 μm, for example, 8 μm.
[0031] In the present invention, in step S2, during the carbonization process, due to the low residual carbon rate of the organic ferric salt, mesopores will be preferentially generated around it, and the organic ferric salt will also be converted into ferric oxide accordingly; further, during activation, due to the open-pore characteristics of the mesopores, a good microporous dispersion structure will be further generated around them, and this dispersion structure of micropores and mesopores can greatly inhibit expansion; finally, the ferric oxide generated by the carbonization of the organic ferric salt is dispersed on the surface of the porous carbon and / or in the pores of the mesopores in the form of nanoparticles.
[0032] In some embodiments, in step S2, the carbonization is performed in a protective gas.
[0033] Wherein, the protective gas is preferably nitrogen.
[0034] The flow rate of the protective gas is preferably 0.5-5 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 .
[0035] In some embodiments, in step S2, the carbonization includes a temperature rising stage and a temperature keeping stage.
[0036] The heating rate in the heating stage is preferably 1-10°C / min, such as 4°C / min.
[0037] The temperature in the insulation stage is preferably 300-550°C, for example 500°C.
[0038] The duration of the heat preservation stage is preferably 0.5-5 h, such as 2 h.
[0039] In some embodiments, in step S2, the first precursor is further cross-linked before the carbonization.
[0040] Wherein, the cross-linking preferably includes a temperature rising stage and a temperature keeping stage.
[0041] The heating rate in the heating stage is preferably 1-10°C / min, such as 4°C / min.
[0042] The temperature in the insulation stage is preferably 100-300°C, for example 200°C.
[0043] The time of the insulation stage is preferably 0.5-2 hours, such as 1 hour.
[0044] In some embodiments, in step S2, the activation method includes gas activation and / or alkali activation.
[0045] Wherein, the gas activation is preferably CO2 activation or water vapor activation.
[0046] In some embodiments, in step S2, the activation method is CO2 activation.
[0047] The flow rate of CO2 is preferably 0.1-10 L·kg -1 ·min -1 , for example 2L·kg -1·min -1 .
[0048] The CO2 activation time is preferably 2-20 hours, such as 9 hours.
[0049] Wherein, the temperature of the CO2 activation is preferably 300-500°C.
[0050] In some embodiments, in step S2, the specific surface area of the second precursor (i.e., porous carbon) is 1800 m 2 / g-2100m 2 / g, micropore surface ratio is 75-98%, mesopore surface ratio is 2%-25%, pore volume is 0.6cm 3 / g-1.5cm 3 / g.
[0051] In the present invention, in step S3, the first vapor deposition is carried out in the presence of silane and nitrogen at the same time, and the deposition of silicon, doping of nitrogen and reduction of metal oxides can be achieved simultaneously. In the first vapor deposition process, silane cracks to produce hydrogen. On the one hand, based on the principle of the Haber process for synthesizing ammonia, ferric oxide catalyzes hydrogen and nitrogen to synthesize ammonia. While the nitrogen is solidified, the ammonia and silane have similar cracking temperatures, so that nitrogen atoms are successfully doped into silicon nanoparticles, especially into silicon nanoparticles with larger particle sizes, so that silicon is transformed from a semiconductor to a conductor, forming an N-type semiconductor, and reducing the ohmic resistance of the silicon nanoparticles; at the same time, part of the nitrogen atoms generate Li-N irreversible compounds in the first lithium insertion process, which expands the lattice stripe structure of the silicon nanoparticles, making it disordered, while reducing the migration impedance of lithium ions, which is beneficial to improve the energy density and rate performance of the battery. On the other hand, hydrogen can be used as a reducing agent to partially or completely reduce the ferric oxide distributed in the porous carbon into nano-iron elemental substance, and then in situ grow carbon nanotubes and carbon coating during the second vapor deposition in step S4.
[0052] In some embodiments, in step S3, the volume ratio of the silicon source gas to the carrier gas is (0.05-1):1, for example, 0.25:1.
[0053] In some embodiments, in step S3, the silane (general formula is Si n H 2n+2 ) may include monosilane (SiH4), disilane (Si2H6), trisilane (Si3H8) and tetrasilane (Si4H 10 )
[0054] In some embodiments, in step S3, the flow rate of the first deposition gas is 0.1-2 L·kg -1 ·min-1 , for example 0.5 L kg -1 ·min -1 .
[0055] In some embodiments, in step S3, the temperature of the first vapor deposition is 400-500°C, for example, 500°C.
[0056] In some embodiments, in step S3, the absolute pressure of the first vapor deposition is 0.1-50 MPa, such as 1 MPa or 5 MPa.
[0057] In some embodiments, in step S3, the first vapor deposition time is 4-16 hours, for example 8 hours. The first vapor deposition time affects the amount of silicon deposition and also affects the degree of reduction of ferric oxide. Preferably, the first vapor deposition time allows the ferric oxide to be completely reduced to elemental iron.
[0058] In the present invention, both ferric oxide and iron element can be catalysts for carbon nanotubes. Because of the presence of ferric oxide and oxygen atoms, its interaction with carbon material is stronger, resulting in the growth of carbon nanotubes in the top growth mode, while the interaction of iron element with carbon material is smaller, resulting in the growth of carbon nanotubes in the bottom growth mode. Compared with the top growth mode, the growth rate of carbon nanotubes in the bottom growth mode is faster, so carbon nanotubes of a longer length will be grown first and then carbon coating will be performed. And the top growth mode is because the catalyst is in the mesopore, resulting in it not being closely in contact with the carbon source gas, so its growth rate is slow, and it is easy to cause the carbon nanotubes grown in the later stage to top-crush the grown carbon shell, making the coating uneven, and also resulting in the foaming and gram capacity and rate performance reduction of the later stage pickling. In addition, in the bottom growth mode, the catalyst is outside the material, and the top growth is inside the material, the former is more conducive to water washing and demagnetization, and the latter is easy to lose more materials in the process of demagnetization, reducing yield, increasing cost, etc.
[0059] In some embodiments, in step S4, the carbon source gas includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates.
[0060] In some embodiments, in step S4, the second deposition gas further includes a carrier gas.
[0061] Wherein, the carrier gas preferably includes nitrogen.
[0062] Wherein, the volume ratio of the carbon source gas to the carrier gas is (0.05-1):1, for example, 0.25:1.
[0063] In some embodiments, in step S4, the flow rate of the second deposition gas is 0.1-50 L·kg-1 ·min -1 , for example 5L·kg -1 ·min -1 .
[0064] In some embodiments, in step S4, the temperature of the second vapor deposition is 400-800°C, for example, 500°C.
[0065] In some embodiments, in step S4, the time of the second vapor deposition is 2-40 hours, for example, 10 hours.
[0066] In some embodiments, in step S4, the second vapor deposition further includes washing and drying steps.
[0067] In some embodiments, the washing comprises the steps of washing with hydrochloric acid first and then washing with water. The purpose of the washing is mainly to remove iron-containing substances.
[0068] Wherein, in the hydrochloric acid washing operation, the mass of the hydrochloric acid is preferably 1-100:1 times, for example, 20 times, of the product obtained by the second vapor deposition.
[0069] Wherein, in the hydrochloric acid washing operation, the concentration of the hydrochloric acid is preferably 0.0001-12.9 mol / L, such as 0.1 mol / L.
[0070] Wherein, in the hydrochloric acid washing operation, the number of times of hydrochloric acid washing is preferably 1-10 times, for example, 2 times.
[0071] The hydrochloric acid washing operation may include soaking the product obtained by the second vapor deposition in hydrochloric acid and then filtering; the soaking time is preferably 5-500 minutes, such as 30 minutes.
[0072] Wherein, in the water washing operation, the quality of the water is preferably 1-30 times, for example 3 times, that of the product obtained by the hydrochloric acid washing.
[0073] Wherein, in the water washing operation, the number of times of water washing is preferably 1-10 times, for example 3 times.
[0074] In some embodiments, the drying is performed using a double cone dryer.
[0075] The present invention also provides a silicon-carbon material, which is prepared by the method for preparing the silicon-carbon material as described above.
[0076] In the present invention, the silicon-carbon material may include a core-shell structure, which includes an inner core, an outer shell and carbon nanotubes; the inner core includes porous carbon and silicon particles, and the silicon particles are distributed on the surface and / or in the pores of the porous carbon; the outer shell includes a carbon layer, and the carbon layer is coated on the surface of the inner core.
[0077] In the core-shell structure, the distribution of the carbon nanotubes may include one or more of the following methods ①-⑤:
[0078] ① The carbon nanotubes are distributed in the pores of the porous carbon.
[0079] ② The carbon nanotubes are distributed on the surface of the porous carbon;
[0080] ③ The carbon nanotubes extend from the surface of the porous carbon and penetrate the shell;
[0081] ④ The carbon nanotubes extend from the pores of the porous carbon and penetrate the shell;
[0082] ⑤ The carbon nanotubes extend from the inside of the shell and penetrate the shell.
[0083] In some embodiments, the silicon carbon material has a silicon content of 45%-55%, for example 48.0%, 50.18%, 50.35%, 50.54%, 50.69%, 50.67%, 50.75%, 50.65%, 50.2% or 51.49%.
[0084] In some embodiments, the silicon-carbon material has a carbon content of 45%-55%, such as 49.82%, 49.65%, 49.46%, 49.31%, 49.33%, 49.25%, 49.35%, 49.8%, 48.51% or 52.0%.
[0085] In some embodiments, the powder conductivity of the silicon carbon material is 10-1000 s / cm, for example, 11.4 s / cm, 13.2 s / cm, 32.2 s / cm, 54.1 s / cm, 87.3 s / cm, 134.2 s / cm, 189.6 s / cm, 205.3 s / cm, 213.2 s / cm, 801 s / cm or 91.2 s / cm.
[0086] In some embodiments, the D50 particle size of the silicon-carbon material is 7.5-8.5 μm, for example, 7.7 μm, 7.8 μm, 7.9 μm or 8 μm.
[0087] In some embodiments, the specific surface area of the silicon-carbon material is 3-5 m 2 / g, for example, 3.4m 2 / g, 3.6m2 / g, 3.8m 2 / g, 4m 2 / g, 4.1m 2 / g or 4.3m 2 / g.
[0088] The present invention also provides a lithium ion battery, which comprises the silicon-carbon material as described above.
[0089] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0090] The reagents and raw materials used in the present invention are commercially available.
[0091] The positive and progressive effects of the present invention are:
[0092] The present invention combines nitrogen doping of silicon nanoparticles, mesopore etching control, mesopore strengthening, and growth of carbon tubes on the silicon-carbon surface, and adopts a simple process to comprehensively optimize the electrical conductivity, compressive strength and other properties of the obtained silicon-carbon material. When used in lithium-ion batteries, it can ensure a relatively high capacity while effectively alleviating expansion, and comprehensively optimize its first efficiency, rate performance, cycle performance and other properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0093] Figure 1 It is a structural schematic diagram of the distribution of mesopores and micropores during the preparation process of the silicon-carbon material in the present invention.
[0094] Figure 2 Schematic diagram of the structure of the silicon-carbon material with carbon nanotubes grown on the top in Examples 1-4.
[0095] Figure 3 This is a schematic diagram of the structure of the silicon-carbon material with carbon nanotubes grown at the bottom in Example 5-8. DETAILED DESCRIPTION
[0096] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0097] Example 1
[0098] The silicon-carbon material is prepared according to the following steps:
[0099] S1. Preparation of the first precursor:
[0100] 1 kg of phenolic resin (2153 type, provided by Hubei Hengye Technology Co., Ltd.), 2 kg of ethanol, 60 g of hexamethylenetetramine (HMT), and 5 g of ferric citrate (the molar amount of iron is 0.02 mol) were mixed and homogenized with a high-speed dispersing homogenizer at a dispersing speed of 2000 r / min for 60 min. Spray drying was performed at 130° C. until the particle diameter was 8 μm, thereby obtaining a first precursor.
[0101] S2. Preparation of the second precursor (i.e. porous carbon):
[0102] (1) Cross-linking: The first precursor was placed in a rotary furnace at a speed of 10 r / min, a heating rate of 4 °C / min, and a temperature of 2 L·kg -1 min -1 Nitrogen was introduced at a flow rate of , the temperature was raised to 200°C and then kept warm for 1h.
[0103] (2) Carbonization: Continue heating at a rate of 4 °C / min and at 1 L·kg -1 min -1 Nitrogen was introduced at a flow rate of , the temperature was raised to 500°C and then kept warm for 2h.
[0104] (3) Activation: CO2 was introduced and activated under CO2 atmosphere at a flow rate of 2 L kg -1 min -1 , the furnace temperature is 500℃, the activation time is 9h, and the second precursor (i.e. porous carbon) is obtained. At this time, ferric citrate has generated nano-iron trioxide.
[0105] S3. Preparation of the third precursor:
[0106] First vapor deposition: The atmosphere was switched to a mixture of monosilane and nitrogen (20% monosilane and 80% nitrogen by volume) with a flow rate of 0.5 L kg -1 min -1 , absolute pressure of 1 MPa, deposition at 500 °C for 8 h, silicon deposition, nitrogen doping and metal oxide reduction.
[0107] S4. Preparation of silicon-carbon materials:
[0108] (1) Second vapor deposition: The atmosphere was switched to a mixture of acetylene and nitrogen (20% acetylene and 80% nitrogen by mass) at a flow rate of 5 L kg -1 min -1 , deposited at 500 °C for 10 h;
[0109] The gas was then switched to nitrogen and the temperature was then lowered to room temperature, 25°C.
[0110] (2) Washing and drying: Then, 0.1 mol / L hydrochloric acid is used to soak the product obtained in the previous step in an amount of 20 times (by mass) for 30 minutes, filtered, and washed twice; then, deionized water is used to wash three times. Then, a double cone drying machine is used to dry the powder washed with deionized water, and then sealed and stored to obtain the silicon-carbon material of this embodiment.
[0111] Example 2
[0112] On the basis of Example 1, only the amount of ferric citrate in step S1 was changed to 10 g (the molar amount of iron was 0.04 mol), and the remaining steps and parameters were the same as Example 1, to obtain the silicon-carbon material of Example 2.
[0113] Example 3
[0114] On the basis of Example 1, only the amount of ferric citrate in step S1 was changed to 15 g (the molar amount of iron was 0.06 mol), and the remaining steps and parameters were the same as Example 1, to obtain the silicon-carbon material of Example 3.
[0115] Example 4
[0116] On the basis of Example 1, only the amount of ferric citrate in step S1 was changed to 20 g (the molar amount of iron was 0.08 mol), and the remaining steps and parameters were the same as Example 1, to obtain the silicon-carbon material of Example 4.
[0117] Example 5
[0118] On the basis of Example 1, only the amount of ferric citrate in step S1 is changed to 25 g (the molar amount of iron is 0.1 mol), and the remaining steps and parameters are the same as Example 1, to obtain the silicon-carbon material of Example 5.
[0119] Example 6
[0120] On the basis of Example 1, only the amount of ferric citrate in step S1 was changed to 30 g (the molar amount of iron was 0.12 mol), and the remaining steps and parameters were the same as Example 1, to obtain the silicon-carbon material of Example 6.
[0121] Example 7
[0122] On the basis of Example 1, only the amount of ferric citrate in step S1 was changed to 35 g (the molar amount of iron was 0.14 mol), and the remaining steps and parameters were the same as Example 1, to obtain the silicon-carbon material of Example 7.
[0123] Example 8
[0124] On the basis of Example 1, only the amount of ferric citrate in step S1 was changed to 40 g (the molar amount of iron was 0.16 mol), and the remaining steps and parameters were the same as Example 1, to obtain the silicon-carbon material of Example 8.
[0125] Example 9
[0126] On the basis of Example 1, only the ferric citrate in step S1 is changed to ferric acetate, and the amount used is 37.2 g (the molar amount of iron is 0.25 mol), and the remaining steps and parameters are the same as Example 1, to obtain the silicon-carbon material of Example 9.
[0127] Example 10
[0128] On the basis of Example 1, the amount of ferric citrate in step S1 is changed to 20 g (the molar amount of iron is 0.08 mol), and the absolute pressure in step S3 is changed to 5 MPa. The remaining steps and parameters are the same as in Example 1, and the silicon-carbon material of Example 10 is obtained.
[0129] Embodiment 11
[0130] On the basis of Example 1, only the absolute pressure in step S3 is changed to 0.1 MPa, and the remaining steps and parameters are the same as Example 1, to obtain the silicon-carbon material of Example 11.
[0131] Comparative Example 1
[0132] On the basis of Example 1, ferric citrate is not added in step S1, and monosilane is used to replace the mixed gas of monosilane and nitrogen in step S3. The remaining steps and parameters are the same as those in Example 1, and the silicon-carbon material of Comparative Example 3 is prepared.
[0133] Comparative Example 2
[0134] On the basis of Example 1, ferric citrate was not added in step S1, but was replaced by 60 g of melamine, and the remaining steps and parameters were the same as those in Example 1, to obtain the silicon-carbon material of Comparative Example 2.
[0135] Comparative Example 3
[0136] On the basis of Example 1, monosilane is used to replace the mixed gas of monosilane and nitrogen in step S3, and the remaining steps and parameters are the same as those in Example 1, to obtain the silicon-carbon material of Comparative Example 3.
[0137] Comparative Example 4
[0138] On the basis of Example 1, 60 g of melamine was added to the slurry in step S1, and monosilane was used to replace the mixed gas of monosilane and nitrogen in step S3. The remaining steps and parameters were the same as those in Example 1, and the silicon-carbon material of Comparative Example 4 was prepared.
[0139] Effect Example
[0140] The following effect tests were performed on the intermediate products and the final silicon-carbon materials in Examples 1-11 and Comparative Examples 1-4 respectively:
[0141] 1. Electrochemical performance test
[0142] (1) Button battery preparation
[0143] Preparation of negative electrode slurry and pole piece: The negative electrode formula is designed as CMC:PAA:SBR:SP:CNTs:silicon-carbon material:graphite=0.5:2.5:1:0.1:15:80.9, and the time flow of negative electrode slurry preparation is graphite→CMC→silicon-carbon material→SP→CNTs. After that, it is dispersed for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution of 1000r / min. Then, deionized water with a solid content of 40% is injected at one time (only 80% of the amount is added), and it is dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 600r / min. PAA is added and dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 500r / min. The remaining 20% of deionized water is injected, and finally SBR is added and dispersed for 1 hour at a rotation speed of 300r / min and a revolution of 300r / min. The coated current collector is 8 μm thick copper foil, coated on both sides, with the coated side facing the negative electrode of the button battery. The thickness of the active material coated on one side is about 40 μm, and the compaction density is 1.8 g / cm 3 (Punch the electrode into a unit circle, test the weight, subtract the weight of the copper foil, and divide it by the thickness to get the compaction density), where the coating speed is 40cm / s, the baking temperature is 80°C, and the drying time is 400s.
[0144] Preparation of battery electrolyte: The electrolyte composition, by mass percentage, is as follows: the formula is EC 10%, PC 15%, DEC 20%, PP 30%, LiPF6 15%, FEC 6%, PS 2.5% and LiODFB 1.5%.
[0145] Half-cell preparation: The positive electrode uses the above single-piece negative electrode plate, the negative electrode uses a lithium sheet, 0.5g of the above electrolyte, assembled into a CR2450 button cell, and the voltage serial port uses 0-1.5V. The entire battery is assembled in a glove box to avoid contact with air.
[0146] (2) Test parameters and steps
[0147] ① Gram capacity and number of cycles to failure
[0148] 1.5V Gram Capacity:
[0149] The button cell was discharged at a constant voltage of 0.1 V / h to 0.000 V, and then charged at 0.1 V / h to 1.5 V, and the charging capacity was recorded. After the capacity was obtained, the capacity / mass of active matter in the electrode was used to obtain the gram capacity at 0.1C 1.5V.
[0150] 0.5C 1.5V cycle failure number (measured at 25℃ and 45℃ respectively):
[0151] Reassemble a button battery and perform a constant current charge and discharge test at 0.5C of the charging capacity, repeatedly charge and discharge from 0v to 1.5v, terminate when the discharge gram capacity is 60% of the 1.5V gram capacity, and record the number of cycles, which is the number of cycles to failure under the test conditions.
[0152] 1C 1.5V cycle failure number (measured at 25℃ and 45℃ respectively):
[0153] Reassemble a button battery and perform a constant current charge and discharge test with a charging capacity of 1C, repeatedly charging and discharging from 0v to 1.5v, and terminate when the discharge gram capacity is 60% of the 1.5V gram capacity, and record the number of cycles, which is the number of cycles to failure under the test conditions.
[0154] ②Rate retention rate
[0155] 25℃ different rate retention rate (%): at 25℃, 1C rate cycle failure number / 0.5C rate cycle failure number.
[0156] 45℃ different rate retention rate (%): at 45℃, 1C rate cycle failure number / 0.5C rate cycle failure number.
[0157] 0.5C hot box cycle retention rate (%): 0.5C 45℃ cycle failure number / 0.5C 25℃ cycle failure number.
[0158] The difference in magnification at 45°C and 25°C (%): 45°C different magnification retention rate - 25°C different magnification retention rate.
[0159] ③First effect
[0160] The button battery was discharged at a constant voltage of 0.1 V / h to 0.000 V, then charged at 0.1 / h to 1.5 V, and the charge and discharge capacity was recorded. The initial efficiency was obtained by the ratio of lithium removal capacity to lithium insertion capacity.
[0161] ④ Lithium insertion expansion (measured at 25°C and 45°C respectively)
[0162] Lithium insertion expansion: (thickness of the electrode after saturated lithium insertion - thickness of the copper foil) / (thickness of the electrode without lithium insertion - thickness of the copper foil)-1.
[0163] 2. Physical and chemical properties test of the intermediate products and silicon-carbon materials themselves
[0164] ① Particle size test: carried out using a laser particle size analyzer.
[0165] ② Specific surface area and pore volume test: conducted using ASAP2020 from Micromeritics;
[0166] ③Carbon content and silicon content test: Use high-frequency carbon-sulfur analyzer (model DK-606).
[0167] ④ Iron content test: conducted using an inductively coupled plasma spectrometer (ICP, model Agilent 5800, provided by Agilent).
[0168] ⑤ Raman spectroscopy test (Raman): There are two characteristic peaks in the Raman spectrum curve of silicon-carbon materials, with the peak values located at 1310-1360cm -1 The peak between is the disorder peak (D peak); located at 1560~1610cm -1 The peak between the D peak and the G peak is the graphite peak (G peak). The integrated area ratio of the D peak to the G peak (ID / IG) can be used to characterize the disorder or graphitization degree of the silicon-carbon material. The smaller the ID / IG, the lower the disorder and the higher the graphitization degree, and the stronger the buffering effect of the obtained material on the expansion of silicon-intercalated lithium.
[0169] ⑥ Powder conductivity test: It is carried out using a powder conductivity meter (model FT-8100), based on the four-probe test principle and the test standard is GB / T 1552-1995. A known amount of solid powder of the material to be tested is used, the volume is compressed to a set pressure value or pressure under hydraulic power, and the conductivity of the solid powder is measured online.
[0170] The results are shown in Tables 1 to 3 respectively.
[0171] Table 1
[0172]
[0173]
[0174] Table 2
[0175]
[0176] Table 3
[0177]
[0178]
[0179] It can be seen from the results of Tables 1 to 3 that the silicon-carbon materials obtained in Examples 1-11 have at least lower ID / IG than those in Comparative Examples 1-4. When used in batteries, they have excellent anti-expansion properties and at least better cycle performance, and preferably also have higher first efficiency, higher cycle performance, higher rate performance and higher thermal cycle performance. This shows that the silicon-carbon materials obtained in Examples 1-11 of the present invention can comprehensively optimize the various performance aspects of the obtained batteries.
[0180] Specifically, in Examples 1-11 of the present invention, due to the complexation of the iron salt, the macropores and above in the carbon material precursor will be eliminated first, thereby improving the overall strength. During the carbonization process, due to the low residual carbon rate of the iron salt, mesopores will be preferentially generated around it, and the iron salt will also be converted into metal oxides and attached to the mesopores. Further, during activation, due to the open-pore characteristics of the mesopores, a good microporous dispersion structure will be further generated around them, and the metal oxides will also be dispersed on the surface of the mesopores. Figure 1 As shown. When silicon source gas and nitrogen are introduced for the first vapor deposition, silicon and doped nitrogen will be deposited at the same time, and silane deposition will produce hydrogen. On the one hand, based on the principle of Haber process for synthesizing ammonia, hydrogen and nitrogen synthesize ammonia. While the nitrogen is solidified, the ammonia and silane have similar cracking temperatures, so that the nitrogen atoms are successfully doped into the silicon nanoparticles to reduce the impedance; on the other hand, hydrogen can be used as a reducing agent to partially reduce the metal oxide on the surface of the mesopores to a metal element, and then when the carbon source gas is introduced for the second vapor deposition, carbon nanotubes and carbon coating are grown in situ, and carbon nanotubes are grown in situ from the metal element as much as possible in a bottom-end growth manner; among them, the oxide corresponding to the iron salt (ferric oxide) and the elemental iron are both catalysts for carbon nanotubes, but when the amount of iron salt is small, the amount of ferric oxide is relatively large. Due to the presence of oxygen atoms, its interaction with the carbon material is stronger, resulting in the growth of carbon tubes mainly in a top-end growth manner, as shown in FIG. Figure 2 (Corresponding to the overall structure before pickling in Example 1-4), when the amount of iron salt used is large, the amount of elemental iron is relatively large, and the interaction between iron and carbon material is smaller, resulting in the growth of carbon tubes mainly in the bottom growth mode, such as Figure 3 (Corresponding to the overall structure before pickling in Examples 5-8). And as the amount of iron salt increases gradually, the overall improved performance is also better. When the amount reaches that of Example 4, the effect is optimal.
[0181] In Comparative Example 1, in the absence of added iron salt and nitrogen doping, effective generation of mesopores, effective growth of carbon tubes and effective reduction of ohmic resistance were not carried out, ID / IG was significantly higher, and conductivity was significantly lower. After being used in batteries, the anti-expansion performance was significantly poor, and the first efficiency and cycle performance were significantly reduced.
[0182] In Comparative Example 2, no iron salt was added, and when nitrogen was doped in a conventional form (i.e., a nitrogen source was directly added to the carbon material precursor), effective generation of mesopores and effective growth of carbon tubes were not carried out, ID / IG was significantly higher, and the electrical conductivity was significantly lower. After being used in the battery, the anti-expansion performance was significantly poor, and the first efficiency and cycle performance were significantly reduced; this shows that in the absence of iron salts, even if nitrogen is doped in a conventional manner, the effect of iron salts and trace amounts of nitrogen doping in the embodiments of the present invention cannot be achieved.
[0183] In Comparative Example 3, even though iron salts were added, in the absence of nitrogen doping, the ID / IG was significantly higher and the conductivity was significantly lower. After being used in the battery, the anti-expansion performance was significantly poor, and the first efficiency and cycle performance were significantly reduced, indicating that trace nitrogen doping also has a significant impact.
[0184] In Comparative Example 4, even though iron salts were added, when nitrogen was doped in conventional form (i.e., nitrogen source was directly added to the carbon material precursor), ID / IG was significantly higher and the conductivity was significantly lower, indicating that trace nitrogen doping also had a significant impact. Even if the nitrogen source was added in conventional form, the effect of trace nitrogen doping during deposition could not be achieved.
Claims
1. A method for preparing a silicon-carbon material, characterized in that: The preparation method of the silicon-carbon material comprises the following steps: S1, drying a slurry of a carbonaceous material precursor and an iron salt to obtain a first precursor; wherein the iron salt comprises an organic trivalent iron salt; S2, carbonizing and activating the first precursor to obtain a second precursor; S3, performing a first vapor deposition on the second precursor to obtain a third precursor; Wherein, the first deposition gas used in the first vapor deposition comprises a silicon source gas and a carrier gas; the silicon source gas comprises silane, and the carrier gas comprises nitrogen; S4, performing a second vapor deposition on the third precursor to obtain the silicon-carbon material; Wherein, the second deposition gas used in the second vapor deposition comprises a carbon source gas.
2. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the organic ferric iron salt includes ferric acetate and / or ferric citrate; And / or, in step S1, based on the mass of the carbon material precursor, the molar amount of iron in the iron salt is 0.01-1 mol / kg, for example, 0.02 mol / kg, 0.04 mol / kg, 0.06 mol / kg, 0.08 mol / kg, 0.12 mol / kg, 0.14 mol / kg, 0.16 mol / kg or 0.25 mol / kg; And / or, in step S1, the drying method is spray drying; And / or, in step S1, the drying temperature is 70-200°C, for example, 130°C; And / or, in step S1, the particle size of the first precursor is 4-16 μm, for example, 8 μm.
3. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the carbon material precursor includes resin and / or biomass; Wherein, the resin preferably includes one or more of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine-formaldehyde resin, furan resin, silicone resin, polyester resin, polyamide resin, acrylic resin, polyurethane, vinyl resin, hydrocarbon resin and polyether resin; Wherein, the biomass preferably includes one or more of lignin, cellulose, hemicellulose and chitin; preferably, in step S1, the carbon material precursor includes phenolic resin, and the slurry also includes a curing agent; Wherein, the curing agent preferably includes hexamethylenetetramine; Wherein, the mass ratio of the curing agent to the phenolic resin is preferably (0.005-1):1, for example 0.06:1; And / or, in step S1, the solvent in the slurry preferably includes ethanol; And / or, in step S1, the mass ratio of the solvent in the slurry to the carbon material precursor is preferably (1-20):1, for example, 2:
1.
4. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the carbonization is carried out in a protective gas; Wherein, the protective gas is preferably nitrogen; The flow rate of the protective gas is preferably 0.5-5 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 ; And / or, in step S2, the carbonization includes a heating stage and a heat preservation stage; Wherein, the heating rate in the heating stage is preferably 1-10°C / min, for example 4°C / min; Wherein, the temperature of the insulation stage is preferably 300-550°C, for example 500°C; The time of the insulation stage is preferably 0.5-5h, for example 2h; And / or, in step S2, the first precursor is cross-linked before the carbonization; Wherein, the cross-linking preferably includes a heating stage and a heat preservation stage; The heating rate in the heating stage is preferably 1-10°C / min, for example 4°C / min; The temperature in the insulation stage is preferably 100-300°C, for example 200°C; The time of the insulation stage is preferably 0.5-2 hours, such as 1 hour.
5. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the activation method includes gas activation and / or alkali activation; Wherein, the gas activation is preferably CO2 activation or water vapor activation; Preferably, the gas activation is CO2 activation; The flow rate of CO2 is preferably 0.1-10 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 ; Wherein, the CO2 activation time is preferably 2-20h, for example 9h; Wherein, the temperature of the CO2 activation is preferably 300-500°C.
6. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S3, the volume ratio of the silicon source gas to the carrier gas is (0.05-1):1, for example, 0.25:1; And / or, in step S3, the silane includes one or more of monosilane, disilane, trisilane and butasilane; And / or, in step S3, the flow rate of the first deposition gas is 0.1-2 L·kg -1 ·min -1 , for example 0.5 L kg -1 ·min -1 ; and / or, in step S3, the temperature of the first vapor deposition is 400-500° C., for example, 500° C.; and / or, in step S3, the absolute pressure of the first vapor deposition is 0.1-50 MPa, for example, 1 MPa or 5 MPa; And / or, in step S3, the time of the first vapor deposition is 4-16 hours, for example 8 hours.
7. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S4, the carbon source gas includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates; and / or, in step S4, the second deposition gas further includes a carrier gas; Wherein, the carrier gas preferably comprises nitrogen; Wherein, the volume ratio of the carbon source gas to the carrier gas is preferably (0.05-1):1, for example 0.25:1; And / or, in step S4, the flow rate of the second deposition gas is 0.1-50 L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 ; and / or, in step S4, the temperature of the second vapor deposition is 400-800° C., for example, 500° C.; And / or, in step S4, the time of the second vapor deposition is 2-40 hours, for example 10 hours; And / or, in step S4, the second vapor deposition further includes washing and drying steps; Wherein, the washing step preferably includes the steps of first washing with hydrochloric acid and then washing with water.
8. A silicon-carbon material, characterized in that: The silicon-carbon material is prepared by the method for preparing the silicon-carbon material according to any one of claims 1 to 7.
9. The silicon-carbon material according to claim 8, characterized in that: The silicon-carbon material comprises a core-shell structure, wherein the core-shell structure comprises a core, an outer shell and carbon nanotubes; the core comprises porous carbon and silicon particles, wherein the silicon particles are distributed on the surface and / or in the pores of the porous carbon; the outer shell comprises a carbon layer, wherein the carbon layer is coated on the surface of the core; The distribution of the carbon nanotubes preferably includes one or more of the following methods ①-⑤: ① The carbon nanotubes are distributed in the pores of the porous carbon. ② The carbon nanotubes are distributed on the surface of the porous carbon; ③ The carbon nanotubes extend from the surface of the porous carbon and penetrate the shell; ④ The carbon nanotubes extend from the pores of the porous carbon and penetrate the shell; ⑤ The carbon nanotubes extend from the inside of the shell and penetrate the shell; and / or, the silicon carbon material has a silicon content of 45%-55%, such as 48.0%, 50.18%, 50.35%, 50.54%, 50.69%, 50.67%, 50.75%, 50.65%, 50.2% or 51.49%; and / or, the carbon content of the silicon-carbon material is 45%-55%, for example, 49.82%, 49.65%, 49.46%, 49.31%, 49.33%, 49.25%, 49.35%, 49.8%, 48.51% or 52.0%; and / or, the powder conductivity of the silicon-carbon material is 10-1000 s / cm, for example, 11.4 s / cm, 13.2 s / cm, 32.2 s / cm, 54.1 s / cm, 87.3 s / cm, 134.2 s / cm, 189.6 s / cm, 205.3 s / cm, 213.2 s / cm, 801 s / cm or 91.2 s / cm; And / or, the D50 particle size of the silicon-carbon material is 7.5-8.5 μm, for example, 7.7 μm, 7.8 μm, 7.9 μm or 8 μm; And / or, the specific surface area of the silicon-carbon material is 3-5m 2 / g, for example, 3.4m 2 / g, 3.6m 2 / g, 3.8m 2 / g, 4m 2 / g, 4.1m 2 / g or 4.3m 2 / g.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the silicon-carbon material as claimed in claim 8 or 9.
Citation Information
Patent Citations
Preparation method for silicon-carbon composite cathode material
CN103618073A
Silicon-carbon negative electrode material, preparation method and application thereof
CN113380998A